GRACE Risk Score Predicts 1-Year Mortality in ACS Patients - Hoyle, Brian (MD Conference Express, 2014)
This article discusses the value of the 8-parameter Global Registry of Acute Coronary Events (GRACE) risk score [The GRACE Investigators. Am Heart J 2001] in predicting the 1-year mortality of patients discharged with acute coronary syndrome (ACS).